Diálogos interdisciplinares nas dinâmicas de informação das técnicas e práticas de conservação-restauração de pinturas em museus de arte - Teixeira, Suzi da Costa (2020)
Exploratory research was conducted on the interdisciplinary dynamics involved in the elaboration of conservation-restoration dossiers, one of the most important information supports of restored works, in this case, paintings in art museums. The focus of this study was the information flow that permeates this field and its historical context in Conservation-Restoration, as well as related terminological issues. The progressive institutionalization of Conservation-Restoration in public art museums has developed at the same time as the creation of standards and codes for carrying out this activity, the execution of which is guided by practical and theoretical requirements aimed at filling gaps and achieving excellence in practice. To identify interdisciplinary interactions, information and communication metrics were used. At the core of the analysis were journals in the field and the scientific results of researchers whose academic training and field of action were considered. The results reveal the existence of interdisciplinary interfaces with heritage, art history, museology and archivologie, as well as a marked interdisciplinary spread over different areas of knowledge.